The Teacher’s Emotional Management in Indonesian EFL Context - Sonia Rahmawati; Fuad Abdullah; Asri Siti Fatimah; Arini Nurul Hidayati; Yuyus Saputra (Journal of English Language Studies, 2021)
English in-service teachers tend to encounter various challenges such as resources of teaching-learning (For example, book, additional support materials), learners' discipline, classroom management. Hence, English in-service teachers are required to have the ability in managing their emotions. However, inadequate attention has been devoted to describing teachers' emotional management during teaching in the classroom. To fill this void, this study aimed at describing how the teacher manages her emotions during English language teaching in the classroom. One teacher of Vocational High school in Tasikmalaya participated as a research participant. The finding indicated that (1) Performing Entertaining activities as a strategy of mitigating saturated teaching routine, (2) Self-relaxing and avoiding harsh words during anger, (3) Strategies to reduce the annoyance. The fact is that the teacher has her way of managing their emotion during teaching in the classroom to continue to do her job professionally.